Проблеми та перспективи розвитку державного регулювання фінансового механізму національної економіки - Умєрова, З.Е. (Культура народов Причерноморья, 2013)
У статті досліджено основні проблеми державного регулювання фінансового механізму країни, які вимагають першочергового їх рішення, щодо аналізу та розвитку фінансового механізму державного регулювання у перспективі. Визначено роль і цілі, а також вплив держави на становлення фінансового механізму країни і обгрунтовано практичні підходи у вирішенні проблем фінансового механізму державного регулювання. The article considers the main problems of state regulation of the financial mechanism of the country (which need priority for solving them) and analyses the development of the financial mechanism of state regulation in the future. The role and goals, as well as the influence of the state on the formation of the financial mechanism of the country are defined, the practical approaches in solving the problems of the financial mechanism of state regulation are proved. Finances are the driving force of the economy. The successful development of financial relations in Ukraine is possible only in case of favorable conditions are created by state . The state promotes the economic development of the country through the financial mechanism (a variety of financial techniques and instruments). The creation of an effective financial mechanism of the state in perspective, is impossible without examining the main important issues that can impede the further development of the financial mechanism of state regulation of the national economy. В статье исследованы основные проблемы государственного регулирования финансового механизма государства, которые требуют первоочередного ее разрешения, а также проанализировано развитие финансового механизма государственного регулирования в перспективе. Определены роль, цели и влияние государства на становление финансового механизма государства и обоснованы практические подходы в решении проблем финансового механизма государственного регулирования.